BOOSTING PURCHASE INTENTIONS WITH EMOJIS: (How Somethinc's Firm-Generated Content On Social Media X Attracts Consumers) - Rizqi Aina; Maya Ariyanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Emojis have rapidly evolved with the advancement of online communication, becoming a staple in various marketing communications, including Firm-Generated Content (FGC). Despite their prevalence, research on the impact of emojis in FGC, particularly on purchase intentions, remains limited. This study aims to explore the influence of emoji usage in FGC on purchase intentions, focusing on the brand Somethinc in the beauty industry. The study targets followers of Somethinc's account on Platform X, investigating emojis as a dependent variable affecting purchase intentions as an independent variable, with positive affect as a mediator and product type as a moderator. This descriptive research employs a quantitative method using SEM-PLS to analyze data collected via purposive sampling in a one-shot cross-sectional manner. Findings reveal a positive and significant relationship between emojis and purchase intentions, mediated by positive affect. The product type, whether hedonic or utilitarian, moderates the positive affect induced by emojis in FGC. These results highlight the impact of emojis in enhancing positive affect and purchase intentions in FGC.